The Development of Smart Farming System for Sea Lettuce Cultured Process - Wongwut, Kamolwan; Chaisermvong, Chitraporn; Angamnuaysiri, Daungkamol (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2024)
Smart farming is a progressive development that leverages information and communication technology in machinery, equipment, and sensors within network-based hi-tech farm supervision cycles. At the forefront of this is the Internet of Things (IoT), a new technology that enables remote device connectivity for smart farming. This paper sets out to transform the seaweed farming process into an intelligent farm system with water oxygen control and environmental monitoring, all powered by IoT technology. The IoT gateway, built with Node-RED, facilitates device connectivity through an Application Programming Interface, with a Node-RED Dashboard providing real-time data in a graphical format. Experiments have shown that the oxygen control system can be operated using two valves, and a valve system can be controlled through a web application, Node-RED, using IoT technology and Internet network connectivity. The embedded system’s percentage error is configured as not exceeding 5 percent for the water temperature, the air temperature, and the humidity measurement. The Node-RED Dashboard displays real-time data, including node status of valve control oxygen, water temperature, air temperature, humidity, and the switch of the valves control oxygen. The data can be transmitted via a wireless system of devices based on the IoT concept.